Best Answer

5b - 3 - 2b = 6b - 3

3b - 3 = 6b - 3

3b - 6b = 3 - 3

b = 0

More answers

Lvl 1

2

Q: What is 5b-3-2b equals 6b plus 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

27

4+1=5. Plus 4 equals 9. Plus 77685769844446473 equals 77685769844446482. Plus 3 equals 77685769844446485. Plus 8 equals 77685769844446493. Plus 1 equals 77685769844446494. Plus 9870998342523322424 equals 1064785604097768918. Plus 4 equals 1064785604097768922.

59

and the answer is 41

-2 plus 5 equals +3

Related questions

It is: b = -3

27

3(g + 6b + 3r)

This simplifies to 6b = 12 so b = 2. Check: (9 x 2) + 7 = 25, 19 + (3 x 2) = 25 OK

It would be composite because a=1 and b=5 so it would be 3+1+6+5=15, and 15 can be divided by 3 into 5.

No.

42

67 plus 3 equals 70.

3 plus 1 plus 4 equals 8

Yes, -8 plus plus 3 equals -5. The "plus plus" is equivalent to a positive sign, so -8 plus (+3) equals -5.

12

2.5 plus 6 plus 3 equals 2.5 plus 6 plus 3